Exploring Cognitive Domain of Revised Taxonomy Bloom on My Next Words Grade 1 English Textbook - Putu Arsana, Anak Agung; Krisna, I Gusti Ngurah; Putra, Kadek Kardiyasa Tirtana (Journal on Studies in English Language Teaching (JOSELT), 2025)
The purpose of this study is to identify cognitive domain categories included in the textbook used to teach English for first-grade elementary school students in Indonesia. The study's findings can help publishers and educators understand textbook material and determine if more content is needed to achieve national requirements. The identification was based on the revised Bloom's taxonomy, which proposes six degrees of cognitive dimension. The authors adopt the qualitative method. The activities were categorized according to the levels of the cognitive dimensions, and the data were arranged in the data analysis table. The result showed that there were 82 tasks in the textbook. 46 (56,1%) remembering, 12 (14,6%) understanding, 15 (18,3%) applying, 9 (11%) analyzing, 0 (0%) evaluating, and 0 (0%) creating. Moreover, 73 activities were classified as lower order thinking (LOTS) and 9 activities as higher order thinking (HOTS) activities. The main task was remembering which the highest cognitive level listed in the Revised Bloom's Taxonomy. Furthermore, there are considerable differences in how LOTS and HOTS tasks are distributed throughout chapters but some chapters also do not have HOTS. These results imply that students' higher-order thinking skills (HOTS) may not be sufficiently developed by depending just on the textbook.